Maternal Knowledge Description About the Importance of Micronutrient Powder for Children Aged 6-23 Months in Public Health Center 2023 - Almeida Oqui, Serafino de; Gomes, Lidia; Menezes da Silva, Dircia Auxiliadora; Oqui, Maximiano; Soares, Miguel; Gonçalves, Sonia (Rifa'Institute, 2024)
Introduction: Knowledge of nutrient both macronutrient and micronutrient is very important. In this modernization era children still suffer for nutritional deficiency, such as micronutrient deficiency of iron, vitamin A, zinc, and others nutritional deficiency. One of the common factors is, the parents have less knowledge about the importance of micronutrient for their children’s development. UNICEF Timor-Leste had done research in 2020 to collect the data of the children that suffer for micronutrient deficiency, and it shows that the prevalence of micronutrient deficiency is 18% around Timor-Leste. Objective: To describe the knowledge of maternal about the importance of micronutrient powder for children aged 6-23 months in Public Health Center Metinaro, administrative post Metinaro, Díli municipality in 2023. Method: The researcher uses quantitative method with the type of description. The sampling technique uses non-probability with type of accidental sampling. The data analysis technique uses statistic univariate test. Result and Discussion: Through this research the researcher found out that most of the mother have sufficient knowledge and 100% they apply MNR for their children. Conclusion: The researcher conclude that these mothers have enough knowledge about MNR and ready to apply it to their children.